Assessment of river water quality using an expert system - Abdul Ghani, Pauziah Hanum (2010)
This study is to develop an expert system to assess water quality for user to derive at a decision equivalent to an expert decision. The ES-RWQ was developed as simple yet reliable tool to assist user in assessing the status of the water quality and relating it to the source contributing to the water quality problem. The main objective is to build a prototype of ES-RWQ with an assessment method, and the ability to derive to a recommendation on the water quality problem. While the conventional models can provide an inside to the quality problem but being complex issue in itself, an effective method of extracting value added information from all sources to facilitate decisions on the implementation of cost-effective pollution prevention and control measurements still requires expert consultation.